Uso de esketamina en depresión resistente al tratamiento: una revisión exploratoria sistemática - Dueñas Rotta, Claudia Esther (2025)
About one-third of patients with major depressive disorder do not respond to antidepressant therapy, resulting in a condition known as treatment-resistant depression (TRD). The objective of this review is to evaluate the available evidence on the effectiveness and/or efficacy of the drug esketamine as a therapy in cases of TRD, with a primary focus on the sociodemographic and methodological characteristics of the available studies. An exploratory systematic review of the topic was conducted using the key terms “esketamine” and “treatment-resistant depression.” Clinical trials that included efficacy and/or effectiveness outcomes were selected. Sociodemographic information, characteristics of the clinical trials and interventions, results, and individual risk of bias were collected. Thirteen clinical trials were included. Ten different definitions for TRD and three for remission were found. The population included was predominantly white, between 18 and 64 years of age, and without medical-psychiatric comorbidities. It was determined that the preferred route of administration of the drug was intranasal. Three studies favored the short-term efficacy of esketamine, and four indicated the opposite. The most common adverse events were dizziness and dissociation. There are controversial results regarding the efficacy of esketamine in TRD, but most studies agree on the drug's good safety profile. It is concluded that there is no consensus on definitions of TRD or remission, and given the limited variety of samples studied, the results are not generalizable to the actual population.